EFEK SUPLEMEN BESI TERHADAP PENINGKATAN HB DAN INDEK ERITROSIT IBU HAMIL - Tangking Widarsa; Wayan Weta; Ida Ayu Alit Widhiartini (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2012)
To study the e? ect of iron supplement equivalent to 60 mg elemental iron and 0.25 mg folic acid tothe erythrocyte indexes and anemia among pregnant mothers.A pretest-pos! est community trialwas carried out among pregnant mothers who were absent of bleeding history and other blooddisorders and gestation’s age were under 24 weeks. Iron tablets equivalent to 60 mg elementaliron and 0.25 mg folic acid were given to the mothers every day until 8 weeks long. Hb, MCV,MCH, and MCHC were evaluated twice before intervention and a er intervention. The changeswere analyzed using t-test and X2 test at 0.05 signi? cance level.Before intervention, almost 78.23% of pregnant women su? ering from iron de? ciency (MCH <27 pg/cell) and 35.28% were anemic (Hb < 11 g/dl). The proportion of su? ering iron de? ciency and anemia signi? cantly decreased a er intervention (p < 0.05). The proportion of su? eringiron de? ciency decreased to 27.43% and anemia decreased to 9.35%. The mean of Hb, MCH andMCHC signi? cantly increased a er intervention (p < 0.05), but there was no changes on MCV (p> 0.05).More then 2/3 of the pregnant mothers su? ered from iron de? ciency and 1/3 were anemic. Ironsupplement signi? cantly increased the erythrocyte indexes and reduced the prevalence of anemiaamong pregnant mothers. Therefore, it is important to continue iron supplement program and itwill be more e? ective when ? rst introduced at pre-maternal period.